2006
DOI: 10.1128/iai.74.5.2965-2974.2006
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Selection for Neisseria gonorrhoeae Opacity Protein Expression in the Absence of Human Carcinoembryonic Antigen Cell Adhesion Molecules

Abstract: The neisserial opacity (Opa) proteins are phase-variable, antigenically distinct outer membrane proteins that mediate adherence to and invasion of human cells. We previously reported that Neisseria gonorrhoeae Opa protein expression appeared to be selected for or induced during experimental murine genital tract infection. Here we further defined the kinetics of recovery of Opa variants from the lower genital tracts of female mice and investigated the basis for this initial observation. We found that the recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 54 publications
4
44
0
Order By: Relevance
“…Selection of subpopulations of Opa ϩ gonococci occurs early during infection of estradiol-treated female mice, and interestingly, the recovery of Opa ϩ variants over time is cyclical. Consistent with the hypothesis that Opa ϩ and Opa Ϫ populations of bacteria have distinct advantages in vivo, shifts in the predominant Opa phenotype of vaginal isolates are paralleled by fluctuations in the total number of gonococci recovered (52).…”
supporting
confidence: 61%
See 2 more Smart Citations
“…Selection of subpopulations of Opa ϩ gonococci occurs early during infection of estradiol-treated female mice, and interestingly, the recovery of Opa ϩ variants over time is cyclical. Consistent with the hypothesis that Opa ϩ and Opa Ϫ populations of bacteria have distinct advantages in vivo, shifts in the predominant Opa phenotype of vaginal isolates are paralleled by fluctuations in the total number of gonococci recovered (52).…”
supporting
confidence: 61%
“…The factors responsible for the observed associations between Opa phenotype, culture rate, and the menstrual cycle are not known. Salit (49) showed that opaque colonies were more resistant to progesterone than transparent colonies; however, the resultant hypothesis that Opa proteins directly protect gonococci from progesterone was not supported when gonococci with defined Opa phenotypes were tested (52). It is possible that the expression of Opa protein colonization receptors is hormonally regulated.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…These effects could be as simple as the mtrR mutant having a minor growth disadvantage that we did not detect under standard culture conditions, but which was reported to accompany overexpression of other resistance pumps (5). We propose a more complex explanation (121) shown at the top of the figure was used to create strain FA19Cm R as described (177). Strain FA19 Km R was constructed by replacing the cat marker of strain FA19Cm R with the aphA-3 cassette from plasmid pGCCKm, the construction of which is shown in the left side of the figure.…”
Section: Discussionmentioning
confidence: 99%
“…Strain FA19 Km R was constructed by replacing the cat marker of strain FA19Cm R with the aphA-3 cassette from plasmid pGCCKm, the construction of which is shown in the left side of the figure. To construct pGCCKm, a 2.3-kb PCR fragment from pGCC5 was amplified using primers F1-lctP (44) and icatB (177) Briefly, a 760-bp PCR product containing the cat gene from pGCC5 was amplified using primers icatB and icatC (177) and ligated into the BsrBI site within the mtrE gene cloned into pCR-Blunt (pCR-mtrE). Klenow fragment was used to fill in BsrBI ends prior to ligation.…”
Section: Discussionmentioning
confidence: 99%